Dampak Perkembangan Kawasan Wisata Pertanian dan Kerbau Rawa di Kabupaten Hulu Sungai Selatan Provinsi Kalimantan Selatan - Abdul Wahab; Shalihah Shalihah; Iman Setya Budi (Ekonomi Keuangan Syariah dan Akuntansi Pajak, 2025)
The economic development of society in Indonesia provides a positive signal with the emergence of entrepreneurs and the tourism sector which has the potential to provide distribution to the economy, thereby increasing tourist visits. This research aims to describe the impact of developing and managing agricultural and buffalo swamp educational tourism areas. The method used is a descriptive qualitative approach. Data collection techniques use observation, interviews, and documentation. The results show that the agricultural and swamp buffalo educational tourist attraction is that development and management of Weitkawa tourism have experienced a lot of progress starting from its rides, facilities, and services. Wietkawa Tourism is a new tourist attraction managed directly by the Tourism Awareness Group. In terms of tourist locations, Weitkawa is quite strategic and easy to reach compared to other tourist attractions in Hulu Sungai Selatan Regency. The price of tourist entry tickets is relatively expensive for local people but relatively cheap for tourists from the city. The impact of Weitkawa tourism can improve the community's economy, such as opening up job opportunities and reducing unemployment, developing business opportunities for residents, and improving community welfare.